Comparison of three-dimensional digital exoscope to standard operating microscope in minimally-invasive lumbar decompression: A cohort study in a community setting - Daniel E. Fulkerson; Evan Medich; Dale F. Szpisjak; Daniel H. Fulkerson (Interdisciplinary Neurosurgery)
Background: Work-related musculoskeletal disorders are common in spine surgeons in the current operative environment. The digital exoscope is a visualization system for minimally-invasive spine surgery (MISS) with potential ergonomic benefits for the surgeon when compared to the standard surgical microscope. The exoscope is gaining popularity in Europe but remains uncommon the United States outside of large academic centers. Purpose: We report surgical metrics for patients who underwent MISS with use of an exoscope or a standard operating microscope in a community-based neurosurgical practice. Methods: We evaluated 121 patients who underwent one- and two- level minimally invasive lumbar decompressions from 2019 to 2023. Fifty-nine patients underwent surgery with the microscope, and 62 underwent surgery with the exoscope. Patients were categorized by visualization method and number of surgical levels, for a total of four groups. Results: Demographics were largely similar across the exoscope and microscope cohorts. All groups had similar durations of hospitalization and complication rates. Estimated blood loss trended lower in the one-level exoscope group compared to the one-level microscope group, which was statistically significant for patients with BMI > 40. Operating room and surgical times were increased in both exoscope groups compared to the same-level microscope groups by 15–17 % and 17–24 %, respectively. Surgical time for exoscope groups showed a non-significant downward trend of 9–14 % in the later cases of the study period compared to the earlier cases, suggesting the presence of a learning curve. Conclusion: The exoscope is a viable alternative to the surgical microscope for MISS in a community-based neurosurgical practice.